A Cadaveric Comparative Study on the Surgical Accuracy of Freehand, Computer Navigation, and Patient-Specific Instruments in Joint-Preserving Bone Tumor Resections. (13th November 2018) - Bosma, Sarah E.; Wong, Kwok Chuen; Paul, Laurent; Gerbers, Jasper G.; Jutte, Paul C.
Abstract : Orthopedic oncologic surgery requires preservation of a functioning limb at the essence of achieving safe margins. With most bone sarcomas arising from the metaphyseal region, in close proximity to joints, joint-salvage surgery can be challenging. Intraoperative guidance techniques like computer-assisted surgery (CAS) and patient-specific instrumentation (PSI) could assist in achieving higher surgical accuracy. This study investigates the surgical accuracy of freehand, CAS- and PSI-assisted joint-preserving tumor resections and tests whether integration of CAS with PSI (CAS + PSI) can further improve accuracy. CT scans of 16 simulated tumors around the knee in four human cadavers were performed and imported into engineering software (MIMICS) for 3D planning of multiplanar joint-preserving resections. The planned resections were transferred to the navigation system and/or used for PSI design. Location accuracy (LA), entry and exit points of all 56 planes, and resection time were measured by postprocedural CT. Both CAS + PSI- and PSI-assisted techniques could reproduce planned resections with a mean LA of less than 2 mm. There was no statistical difference in LA between CAS + PSI and PSI resections (p = 0.92 ), but both CAS + PSI and PSI showed a significantly higher LA compared to CAS (p = 0.042 andp = 0.034, respectively). PSI-assisted resections were faster compared to CAS + PSI (p < 0.001 ) and CAS (p < 0.001 ). Adding CAS to PSI did improve the exit points, however not significantly. In conclusion, PSI showed the best overall surgical accuracy and is fastest and easy to use. CAS could be used as an intraoperative quality control tool for PSI, and integration of CAS with PSI is possible but did not improve surgical accuracy. Both CAS and PSI seem complementary in improving surgical accuracy and are not mutually exclusive. Image-based techniques like CAS and PSI are superior over freehand resection. Surgeons should choose the technique most suitable based on the patient and tumor specifics.